2016
DOI: 10.1016/j.carbon.2015.10.088
|View full text |Cite
|
Sign up to set email alerts
|

Effective derivatization and extraction of insoluble missing lanthanum metallofullerenes La@C2n (n = 36–38) with iodobenzene

Abstract: Extraction of insoluble metallofullerenes, La@C 2n (n = 36-38), was conducted with dichlorobenzene, chlorobenzene, and iodobenzene as a solvent under reflux condition. When iodobenzene was used, La@C 2n (n = 36-38) was successfully extracted as the corresponding phenyl adducts, such as La@C 72 (C 6 H 5), La@C 74 (C 6 H 5), and La@C 76 (C 6 H 5). The number of isomers of corresponding adducts, La@C 72 (C 6 H 5) and La@C 74 (C 6 H 5), were reduced to one-third of that in 1,2,4-trichlorobenzene-extracts, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Therefore, it is highly possible that Lu 2 @ I h (7)-C 80 is generated together with Lu 2 @ C 2v (5)-C 80 during the arc-discharge process, but it may form insoluble products in the raw soot due to its radical character and thus is absent in the usual solvent extract (Table 2). 5658 As for Lu 2 C 82 , a previous report has revealed that Lu 2 @ C s (6)-C 82 and Lu 2 @ C 3v (8)-C 82 are both lower in energy than any of the Lu 2 C 2 @C 80 isomers (Table 2). 39 Accordingly, for a composition of Lu 2 C 76–82 , Lu 2 @C 2 n is always more stable than the corresponding carbide form Lu 2 C 2 @C 2 n –2 , indicating that the formation of di-EMFs is energetically favorable within this cage size range.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, it is highly possible that Lu 2 @ I h (7)-C 80 is generated together with Lu 2 @ C 2v (5)-C 80 during the arc-discharge process, but it may form insoluble products in the raw soot due to its radical character and thus is absent in the usual solvent extract (Table 2). 5658 As for Lu 2 C 82 , a previous report has revealed that Lu 2 @ C s (6)-C 82 and Lu 2 @ C 3v (8)-C 82 are both lower in energy than any of the Lu 2 C 2 @C 80 isomers (Table 2). 39 Accordingly, for a composition of Lu 2 C 76–82 , Lu 2 @C 2 n is always more stable than the corresponding carbide form Lu 2 C 2 @C 2 n –2 , indicating that the formation of di-EMFs is energetically favorable within this cage size range.…”
Section: Resultsmentioning
confidence: 91%
“…Er@ C 76 (C 6 H 5 ) was prepared in a similar process using iodobenzene as the extraction solvent instead of 1,2,4-trichlorobenzene. 26 The purification process for Er@C 76 (C 6 H 5 ) is shown in Figure S2.…”
Section: Methodsmentioning
confidence: 99%
“…Purified Er@C 72 (C 6 H 3 Cl 2 ) was obtained by high-performance liquid chromatography (HPLC) separation of the products (Figure S1). Er@C 76 (C 6 H 5 ) was prepared in a similar process using iodobenzene as the extraction solvent instead of 1,2,4-trichlorobenzene . The purification process for Er@C 76 (C 6 H 5 ) is shown in Figure S2.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…On the other hand, endohedral metal doping of the fullerene cages can generate a novel class of hybrid molecules named endohedral metallofullerenes (EMFs) (Lu et al, 2012;Popov et al, 2013;Yang et al, 2017;Bao et al, 2018). The interaction between the internal metallic unit and fullerene carbon cages renders the chemistry of EMFs more complicated but also intriguing compared to that of empty fullerenes (Lu X. et al, 2011;Maeda et al, 2016). As a result, the amount of metal-mediated reactions of EMFs lags far behind those of fullerenes and the regioselectivity is just satisfactory with the generation of two or more isomers.…”
Section: Introductionmentioning
confidence: 99%